A Study of the Performance of Vertical Armo-Elements (Vae) Using Experiments in Ground and Monolithic Foundation Models - Kurbonov Bakhodir Irkinovich; Mirzayev Azzamjon Jonuzakovich (Genius Journals, 2023)
Models of a monolithic foundation plate and the ground beneath them were created in order to study the performance of a vertical armo-element (VAE). The article examines the radius of horizontal pressure distribution as well as the sinking of the foundation under the influence of loads that fall from the column to a monolithic foundation and the sinking of the monolithic foundation plate under the influence of loads from the column, on both natural and VAE-reinforced ground
Keywords: vertical armo-element; monolithic foundation; ground, soil; loess